DOZ047.40: Bronchopulmonary and vascular anomalies are frequent in children with esophageal atresia. (24th June 2019) - Lejeune, S; Mee, A L; Petyt, L; Mordacq, C; Sfeir, R; Gottrand, F; Fayoux, P; Deschildre, A; Michaud, L; Thumerelle, C
Abstract: Introduction: Esophageal atresia (EA) is frequently associated with other malformations although few data are available. Objective: Describe tracheobronchial, pulmonary and/or vascular malformations in patients with EA using chest CT scans. Methods: Monocentric retrospective study in children with EA, born between 1996 and 2013, who had a CT scan during their follow-up, reviewed by a pediatric radiologist. Results: Among 234 children with EA, 48 patients underwent a CT scan available for interpretation, among which 69% were performed to explore persistent respiratory symptoms. Thirty-nine children (81%) were type III EA, 13 (27%) had a VACTERL association. Six patients (13%) had a pulmonary malformation: 4 lobar agenesis, 1 right pulmonary aplasia, and 1 congenital cystic adenomatoid malformation. All these patients presented with at least one associated malformation. Combined with the results of laryngotracheal endoscopy ( n = 30), 43 patients (90%) had a tracheobronchial anomaly: tracheomalacia for 40 (83%), tracheal stenosis for 12 (25%), right tracheal bronchus for 2 (4%), communicating bronchopulmonary foregut malformation for 1 (2%). Combined with the results of echocardiography ( n = 47), 7 patients (15%) had an isolated vascular anomaly, 8 (17%) had an isolated congenital heart disease and 7 (15%) had both. CT scans permitted the diagnosis of 6 pulmonary malformations (13%), 15 tracheobronchial anomalies (31%), and 2 vascular anomalies (4%). Only one patient (2%) in our study presented with an isolated EA. Conclusion: Our study confirms the association of tracheobronchial, pulmonary, and vascular anomalies in patients with EA. Contrast-enhanced CT scan is complementary to echocardiography and laryngotracheal endoscopy in the exploration of persistent respiratory symptoms.